2007
DOI: 10.3354/meps330139
|View full text |Cite
|
Sign up to set email alerts
|

Gametogenesis and gonad mass cycles in the common circumpolar Antarctic echinoid Sterechinus neumayeri

Abstract: Polar conditions (low and stable seawater temperature coupled with highly seasonal primary productivity) constrain reproduction in benthic invertebrates. The reproductive cycle of the common Antarctic sea urchin Sterechinus neumayeri was investigated at monthly intervals over a 2 yr period in relation to seasonality of chlorophyll standing stock and ability to feed. Competence to spawn increased gradually throughout the austral winter to peaks in September to November. Gonad mass varied strongly, both seasonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…nanoplankton production, acts as a selective pressure driving a superimposed seasonal reproduction, recent evidence of a multi-year cycle in shell growth of the protobranch bivalve (Román-González et al 2017) suggests the reproductive asynchrony observed in females is not underpinned by environmental factors. Nor can this reproductive pattern be explained by the accepted paradigm of an 18-to 24-month period needed for oogenesis in several other Antarctic invertebrates (Peck et al 2005; for examples see Grange et al 2004Grange et al , 2007Brockington et al 2007;Orejas et al 2007). The reproductive ecology of A. eightsii also differs from other shallow-water and deep-sea nuculanid protobranch bivalves that have a 12-month gametogenic cycle, often with seasonal investment in reproduction (Tyler et al 1992;Nakaoka 1994;Jaramillo and Thompson 2008;Scheltema and Williams 2009).…”
Section: Discussionmentioning
confidence: 98%
“…nanoplankton production, acts as a selective pressure driving a superimposed seasonal reproduction, recent evidence of a multi-year cycle in shell growth of the protobranch bivalve (Román-González et al 2017) suggests the reproductive asynchrony observed in females is not underpinned by environmental factors. Nor can this reproductive pattern be explained by the accepted paradigm of an 18-to 24-month period needed for oogenesis in several other Antarctic invertebrates (Peck et al 2005; for examples see Grange et al 2004Grange et al , 2007Brockington et al 2007;Orejas et al 2007). The reproductive ecology of A. eightsii also differs from other shallow-water and deep-sea nuculanid protobranch bivalves that have a 12-month gametogenic cycle, often with seasonal investment in reproduction (Tyler et al 1992;Nakaoka 1994;Jaramillo and Thompson 2008;Scheltema and Williams 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Sterechinus neumayeri were collected (20-25 m depth) by scuba diving from Winter Quarters Bay, Ross Island, Antarctica (77°50′S, 165°0′E) in November 2013 during their peak spawning period (Brockington et al 2007). For environmental conditions for the site of collection see Kapsenberg et al 2015.…”
Section: Study Species Collection Sites and Spawningmentioning
confidence: 99%
“…Reproduction and other processes are generally lengthier in polar waters. An egg development period of 24 mo appears widespread compared with 12 mo or less in temperate species, and this has been demonstrated in the starfish (Odontaster validus), the ophiuroid (Ophionotus victoriae), the sea urchin (Sterechinus neumayeri), the infaunal bivalve (L. elliptica), the limpet (Nacella concinna), the brachiopod (Liothyrella uva) and the octocoral (Ainigmaptilon antarcticum) (Orejas et al 2002, Brockington et al 2006 and references therein). There are a few exceptions, and the scallop (Adamussium colbecki ) matures its eggs in 1 season (Tyler et al 2003), as do some amphipod species (Clarke 1988) Fig.…”
Section: Antarctic Shelf Benthos and Biodiversitymentioning
confidence: 99%